Model of Cardiomyopathy in Diabetes Mellitus Stage 1 and 2 - Khodjiyev Siroj Salimovich; Idrisova Nadrabegim Juginis kizi; Kaxarov Bolta Abdugafarovich (American Journal of Biology and Natural Sciences, 2025)
Cardiomyopathy is a significant cardiovascular complication of diabetes mellitus (DM), characterized by structural and functional abnormalities of the myocardium. This article explores the development of a comprehensive model to study cardiomyopathy in both stage 1 and stage 2 DM. The progression of hyperglycemia-induced oxidative stress, insulin resistance, and inflammation plays a central role in the pathogenesis of diabetic cardiomyopathy (DCM). We review existing animal, cellular, and computational models to evaluate their relevance and limitations in mimicking human DCM. Building on these foundations, we propose an integrated experimental model that incorporates key physiological and molecular mechanisms observed in stage 1 and 2 DM. The model is validated through experimental studies, demonstrating its utility in simulating myocardial fibrosis, diastolic dysfunction, and metabolic dysregulation. Applications of this model include the testing of pharmacological agents, the study of genetic susceptibilities, and the prediction of disease outcomes in diverse patient populations. This approach aims to bridge the gap between experimental research and clinical practice, offering insights into the early detection, management, and potential therapeutic targets for diabetic cardiomyopathy. This work provides a framework for understanding the complex interplay between diabetes and cardiomyopathy, fostering advancements in both basic research and translational medicine.